(untitled) (Revista Argentina de Musicología, 2012)
This paper studies some features in Gustavo Beytelmann’s work, which connects tango and contemporary western art music. After a brief review of his biography follows a thorough analysis of his piece Otras Voces, based on the original score, the recording by Quatuor Caliente in 2011 and information gathered in several interviews with the composer. The analysis explores its main stylistic highlights and contains graphic examples taken from the score. Aspects explored include the use of instrumental sections, registers, textures and the division and characterization of formal sections. Besides, the study draws upon materials derived from western art music and schematizes several tango features. This study aims to contribute to the research on new creations related to the tango genre, hoping that the resources and compositional techniques used in Beytelmann’s music will be a reference for new generations.